2019
DOI: 10.1002/cncr.32151
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survivors’ access to care and quality of life: Do sexual minorities fare worse than heterosexuals?

Abstract: BACKGROUND: Adults with poor access to care are known to have worse quality of life (QOL). The purpose of the current study was to determine differences in cancer survivors' access to care by sexual orientation and to examine the association between access to care and QOL. METHODS: The current secondary data analysis used 4 years of Behavioral Risk Factor Surveillance System data regarding adult men and women who self-reported a history of cancer. Among the 70,524 cancer survivors, a total of 1931 selfidentifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…WSW also reported that female partners were a singular and valuable source of support and were able to perceive partner distress, manage home and caretaking, and share a life beyond cancer [ 24 ]. In addition, WSW reported being less focused on body image, suffered fewer identity issues due to breast cancer and chose not to have reconstruction more often than heterosexual peers [ 22 , 29 , 30 ]. However, WSW reported more challenges with access to care [ 31 ] and experienced more physical complications related to mastectomy and radiation than heterosexual peers [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…WSW also reported that female partners were a singular and valuable source of support and were able to perceive partner distress, manage home and caretaking, and share a life beyond cancer [ 24 ]. In addition, WSW reported being less focused on body image, suffered fewer identity issues due to breast cancer and chose not to have reconstruction more often than heterosexual peers [ 22 , 29 , 30 ]. However, WSW reported more challenges with access to care [ 31 ] and experienced more physical complications related to mastectomy and radiation than heterosexual peers [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…Limitations: Data collected only from one state; self-reported nature of the data. Boehmer et al (2019) [ 30 ] USA BRFSS respondents who had a past diagnosis of cancer ( n = 68,593 heterosexual women, n = 1,931 WSW) Quantitative Secondary data analysis of 2014-2017 years of BRFSS data. Survivors were categorized with an access deficit if any one of the following were true: no health insurance, delaying care, avoiding care due to cost, and lacking a trusted physician.…”
Section: Appendixmentioning
confidence: 99%
“…18 Yet, a study using state-level Behavioral Risk Factor Surveillance System data found that nonheterosexual, or sexual minority women (SMW), survivors with less health care access reported poorer physical and mental quality of life than heterosexual women. 19 Other studies have demonstrated differences in specific components of HRQoL, including perceived stress 20 and selfreported health 21,22 ; however, no published studies have assessed differences in financial or social quality of life between heterosexual and LBW cancer survivors.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, WSW reported being less focused on body image, suffered fewer identity issues due to breast cancer and chose not to have reconstruction more often than heterosexual peers [14,25,54]. However, WSW reported more challenges with access to care [23] and experienced more physical complications related to mastectomy and radiation than heterosexual peers [18]. Counter to other studies, one study demonstrated an association between degree of "outness" (de ned in the study as the number of relationships in which people were open about their identity) and higher distress [30], which may suggest increased experiences of stigmatization when people were open about their identities.…”
Section: Breast Cancer Survivorshipmentioning
confidence: 99%